Generation and UV-VIS-NIR spectral responses of organo-mineral aerosol for modelling soil derived dust. (March 2017) - Utry, N.; Ajtai, T.; Pintér, M.; Illés, E.; Tombácz, E.; Szabó, G.; Bozóki, Z.
Abstract: Various optical properties of laboratory constructed clay minerals coated by humic acid were determined in this study. For the preparation of organo-clay complexes, an adsorption method was conducted in Ca 2+ dominated aquaeous solutions, which provides the opportunity to generate solely internally mixed aerosol particles with complete surface covering. The wavelength dependent optical absorption and scattering coefficients of the syntetised organo-clay complexes and the single clay components were measured in-situ in aerosol phase, using multi-wavelength photoacoustic and scattering instruments. Other climate relevant optical properties such as mass absorption and scattering coefficients, absorption enhancement factor, the imaginary part of complex refractive index, single scattering albedo and coating thickness were also deduced from the measured data. The estimated thickness of humic acid coating was about 10–20 nm. Even such relatively thin shell substantially enhanced the measured absorption of the clay particles with an enhancement factor of about 3–7 in the visible-near ultraviolet range, while caused smaller changes in the mass scattering values. As a cumulative effect, the coating decreased the single scattering albedo of the clay particles; from 0.99 ± 0.04 to 0.93 ± 0.04 in case of illite and from 0.99 ± 0.04 to 0.90 ± 0.03 in case of kaolin at 525 nm. The HA coating slightly modified the shape, the particles became less excentric. We presented a new method capable of generating solely internally mixed particles. Applying this method we experimentally demonstrated the strong effect of a light absorbing coating on the optical properties of dust particle. Highlights: Complete monolayer coating of humic acid (HA) was created on clay particles. Freshly emitted soil derived dust can be modelled by this method. Absorption EF, κ of complex refractive index, SSA, coating thickness were determined. Coating promotes the dispersion of particles and cause EF∼6–7 in the UV–VIS range. Base soluble HA fraction of MD may have important role in global radiative transfer.